Developing a Global Pandemic Exit Strategy and Framework for Global Health Security 2021
DOI: 10.26911/icphmedicine.fp.08.2021.09
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effect in Red Ginger (Zingiber Officinale Var. Rubrum) Extract during the COVID-19 Pandemic

Abstract: Background: Ginger (Zingiber officinale (L.) Rosc) has been used as spice for over 2000 years. Its roots and the obtained extracts contain polyphenol compounds (6-gingerol and its derivatives), which have a high antioxidant activity. Methods for the characterization of antioxidants are presented and illustrated by their application to commercial ginger preparations, since it has been widely speculated that ginger might be beneficial to human health because it exerts antioxidant activity. This study aimed to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…In contrast, in the T1, T2, and T3 treatments, the IC50 value was less than 50 ppm, which means that the antioxidant activity in this treatment was potent. The IC50 value of red ginger oleoresin nanoemulsion in the T1, T2, and T3 treatments was smaller than the red ginger extract in Sholikhati et al [29], namely 41.27 ppm. That is, the antioxidant activity of red ginger in nanoemulsion form is stronger when compared to red ginger extract.…”
Section: Antioxidant Activity Of Red Ginger Oleoresin Nanoemulsionmentioning
confidence: 60%
“…In contrast, in the T1, T2, and T3 treatments, the IC50 value was less than 50 ppm, which means that the antioxidant activity in this treatment was potent. The IC50 value of red ginger oleoresin nanoemulsion in the T1, T2, and T3 treatments was smaller than the red ginger extract in Sholikhati et al [29], namely 41.27 ppm. That is, the antioxidant activity of red ginger in nanoemulsion form is stronger when compared to red ginger extract.…”
Section: Antioxidant Activity Of Red Ginger Oleoresin Nanoemulsionmentioning
confidence: 60%
“…Rubrum has long been used in Indonesian herbal medicine. Many studies have confirmed the anti-inflammatory (Fikri et al, 2016), antioxidant (Sholikhati et al, 2022), antiemetic (Hartati et al, 2022), antibacterial (Assegaf et al, 2020), and antidiabetic (Eliza Arman, 2016) properties of red ginger.…”
Section: Introductionmentioning
confidence: 95%
“…Gingerol and 6-gingerol are the main components of oleoresin that are sensitive to heat, light, and oxygen. Gingerol and shogaol are the sources of ginger's spicy and pungent flavor (Sholikhati et al, 2021).…”
Section: Introductionmentioning
confidence: 99%